KEPEMILIKAN MANAJERIAL TERHADAP PAJAK PENGHASILAN TERUTANG MELALUI DISCRETIONARY ACCRUALS - Kiswanto Kiswanto; Ahmad Nurkhin (Jurnal Keuangan dan Perbankan, 2013)
Governments efforts to boost revenue from the tax sector brought considerable consequences for businessmen.This made businessmen try to do tax planning, one of which was to conduct earnings management to reducepayable taxes . This study examined whether managerial ownership influenced the amount of payable incometax of corporate taxpayers through discretionary accruals. This study used path analysis approach (PathAnalysis) by taking sample of companies listed on the Indonesia Stock Exchange in 2009. The results showedthat managerial ownership directly influenced the payable income tax. Furthermore, it could be seen thatmanagerial ownership had a direct effect on earnings management. Besides, earnings management had a directeffect on payable income tax. Thus, the Sobel test was used to prove the ability of earnings managementvariables in mediating the effect of managerial ownership on income tax. Future research was expected toexpand the main object of observation payable income tax as an tax obligation to ensure that the behavior of thecompany in doing profit or income management for lowering profit or income could lower or raise the payableincome tax.